British Isles survey of multiple sclerosis in twins: MRI. Issue 4 (April 1994) - Thorpe, J W; Mumford, C J; Compston, D A; Kendall, B E; MacManus, D G; McDonald, W I; Miller, D H
Abstract : 64/105 subjects who have a twin with multiple sclerosis included in a study of clinical concordance also underwent MRI of the brain. 8/23 monozygotic and 1/41 dizygotic co-twins from this subgroup were clinically concordant of whom 8/9 had MRI appearances typical of multiple sclerosis. Of the 48 clinically discordant twins aged less than 60, abnormalities on MRI were detected in 6/15 (40%) monozygotic and 13/33 (39%) dizygotic twins compared with 7/37 (19%) healthy age-matched controls. Abnormalities on MRI typical of multiple sclerosis (defined by the Fazekas criteria) were, however, present in only 2/15 (13%) monozygotic and 3/33 (9%) dizygotic twins and 0/37 controls. These results suggest that about 10% of monozygotic and dizygotic twins have "subclinical multiple sclerosis". It is likely that most of the MRI abnormalities seen in clinically discordant twins, however, represent incidental pathology.